"Candidatus Phytoplasma asteris" and "Candidatus Phytoplasma mali" strains infecting sweet and sour cherry in the Czech Republic. Issue 1 (26th October 2017) - Fránová, Jana; Lenz, Ondřej; Přibylová, Jaroslava; Špak, Josef; Koloniuk, Igor; Suchá, Jana; Paprštein, František
Abstract: A survey for phytoplasma diseases was conducted in a sweet and sour cherry germplasm collection and in cherry orchards within the Czech Republic during 2014–2015. Phytoplasmas were detected in 21 symptomatic trees. Multiple infections of cherry trees by diverse phytoplasmas of 16SrI and 16SrX groups and 16SrI‐A, 16SrI‐B, 16SrI‐L, 16SrX‐A subgroups were detected by restriction fragment length polymorphism (RFLP). Nevertheless, phylogenetic analysis placed subgroups 16SrI‐B and 16SrI‐L inseparable together onto one branch of phylogenetic tree. This is the first report of subgroups 16SrI‐A and 16SrI‐L in Prunus spp., and subgroup 16SrX‐A in sour cherry trees. Additionally, novel RFLP profiles for 16SrI‐A and 16SrI‐B‐related phytoplasmas were found in cherry samples. Phytoplasmas with these novel profiles belong, however, to their respective 16SrI‐A or 16SrI‐B phylogenetic clades.